Nitrogen Use Efficiency of Coffee at the Vegetative Stage as Influenced by Fertilizer Application Method - Salamanca-Jimenez, Alveiro; Doane, Timothy A.; Horwath, William R. (Frontiers in Plant Science, 2017)
Nitrogen (N) is the most limiting nutrient for coffee production in Colombia. An adequate supply is especially important during the vegetative period of growth, since any deficiency during this short period is known to have lasting effects on subsequent coffee bean production. Urea fertilizer is commonly applied on the soil surface since steep slopes hamper incorporation into soil, a practice which increases the risk of N volatilization. Little information is available on N recovery during early growth stages under different fertilizer application practices. The aim of this study was therefore to provide a comparison of 15N uptake during the early vegetative growth stage under surface-applied and incorporation practices at two contrasting locations. The highest proportion of plant N derived from fertilizer (Ndff) occurred 60 days following application at the site with greater precipitation and soil organic matter, where surface application also increased the Ndff in roots and stems after 120 days. Although fertilizer N supplied approximately 20-29% of total plant N after four months, this fertilizer-derived N corresponded on average to only 5% of the total application, indicating that very little fertilizer (relative to how much is applied) reaches plants during this time. Apart from the difference in Ndff observed at the wetter site, there was no effect of application method on dry weight and macronutrient content in different plant components, root to shoot ratio, and leaf 13C content. However, site effects were registered for most of these measurements, with the exception of total nutrient uptake. Similarly to Ndff trends, lower root/shoot ratio and higher concentrations of N, K and Mg in aboveground biomass were found in the site with higher rainfall and soil organic matter, likely resulting from higher soil water and N availability. These findings provide new information useful as a direction for further research looking forward increasing NUE during the vegetative stage in Colombian coffee crops.